Consumers' perspective towards cosmetic products in Malaysia: a qualitative interview study - Ab. Hadi, Hazrina; Ayob, Nurain; Awadh, Ammar Ihsan Jawad (2016)
OBJECTIVES: Cosmetic products are used by various segments of society. Hence, the perspectives of these segments towards cosmetic products may differ from each other. this study aimed to explore consumers’ perspectives towards cosmetic products. METHODS: A qualitative study approach was adopted in Kuantan, Pahang. An interview guide was developed with a set of twelve semi-structured questions. Three pharmacists were assigned to validate the questions, and it was translated into Bahasa Malaysia via multistep translation. Purposive sampling was used to recruit participants, and in-depth face-to-face interviews were conducted with 30 participants until the point of saturation was reached. All of the interviews were tape-recorded and transcribed verbatim. RESULTS: Thematic content analysis derived four major themes. Awareness about cosmetic products among the participants was found to be low, but the participants expressed positive perceptions of natural cosmetic products; quality was seen as synonymous with branded products and halal certification. The main criteria which influenced participants towards cosmetics use were the ingredients, the product brand and halal certification. Based on the participants’ personal experiences, complaints and suggestions for the enhancement of cosmetic product quality were also provided. CONCLUSIONS: In conclusion, unsatisfactory awareness related to cosmetic products in Malaysia was noted among the participants in this study. Although, at the time of the study, they were using conventional cosmetic products, the participants in this study showed a positive perception and attitude towards natural cosmetic products. However, the price and accessibility of natural cosmetic products may influence their purchase of cosmetic products.